(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Foreign direct investment (FDI) serves as a facilitating factor for economic growth of various countries. FDI has been associated with the growth and development of a country. By the higher growth rate, a host country can attract FDI in large amount. Foreign exchange reserve is the reserve of foreign currencies held by the central bank of a country for manage their currencies ’value and for the payment of their liabilities. In this research paper, growth rate of forex reserve and growth rate of FDI is studied. The relationship between FDI and FOREX reserve is computed with the help of correlation. For this, secondary data is used from 2001 to2018.